2018
DOI: 10.1002/cre2.148
|View full text |Cite
|
Sign up to set email alerts
|

Examining the perceived versus the actual knowledge about forensic odontology: A cross‐sectional survey among dentists

Abstract: Dentists should have the basic essential skills and knowledge about forensic odontology, to better collaborate with law enforcement and investigations. The objective of this survey was to assess the perceived and actual knowledge toward forensic odontology among dentists and to question their willingness to attend training courses on this specialty. A cross‐sectional survey based on a self‐administered questionnaire was conducted in various districts of Saudi Arabia. Four hundred dentists responded to a questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…A study done by Almutairi et.al showed that dentists had high level of knowledge on most of the important aspects of forensic dentistry, which are investigations of physical violence, estimation of individuals' age and bite-mark analyses but dentists had knowledge deficiencies that were mainly related to the significance of forensic odontology on other aspects such gender discrimination and childneglect investigations. [14] According to a study done by Avon et.al, a forensic dentistry plays a major role in identification of those individuals who cannot be identified visually or other means. The unique nature of our dental anatomy and the placement of custom restorations ensure accuracy when the techniques are correctly employed.…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Almutairi et.al showed that dentists had high level of knowledge on most of the important aspects of forensic dentistry, which are investigations of physical violence, estimation of individuals' age and bite-mark analyses but dentists had knowledge deficiencies that were mainly related to the significance of forensic odontology on other aspects such gender discrimination and childneglect investigations. [14] According to a study done by Avon et.al, a forensic dentistry plays a major role in identification of those individuals who cannot be identified visually or other means. The unique nature of our dental anatomy and the placement of custom restorations ensure accuracy when the techniques are correctly employed.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Australia showed the empirical role of forensic odontologists in disaster management and victim identification and is fulfilled by maintaining comprehensive, well–structured, and accurate dental records for both research teaching purposes, as well as for medicolegal matters. [16] Al Azri et al . conducted a study which suggested the need of record keeping guidelines and practices to increase the level of details, extent, and period of retention of records so that the information needs of forensic odontology activities are met.…”
Section: Discussionmentioning
confidence: 99%
“…The study questions were taken from a previous study. [ 20 , 21 ] A pre-validated questionnaire written in English was distributed online. The legal professionals were asked voluntarily to participate in the study, and confidentiality was to be respected.…”
Section: Methodsmentioning
confidence: 99%